An improved automated method for the measurement of red cell 2,3-diphosphoglycerate. - Purcell, Y (1976)
A modified automated colorimetric micromethod for the determination of red cell 2,3-diphosphoglycerate (2,3-DPG) adapted from that of Grisolia et al (1969) is described. In the modified method, ethylenediaminetetra-acetic acid (EDTA) is not used and consequently concentrations of several reagents are changed. During the development of the method it was found that the presence of EDTA, either in the blood or in reagents, consistently reduced the measured value of 2,3-DPG by 15%. This effect of EDTA, not previously recognized, is independent of the EDTA concentration within the range of 5 to 50 mmol/1 and is at present unexplianed. In normal subjects (41 men and 30 women) the mean red cell 2,3-DPG was 14-5 mol/g haemoglobin (range 12-1-18-1 mol/g haemoglobin). There was no significant difference in 2,3-DPG concentrations between male and female subjects.